The effect of productivity on liquidity under financial frictions - Stefanus Hugo Lusida; Kim Sung Suk (Jurnal Keuangan dan Perbankan, 2019)
Productivity is something that can affect the distribution of the characteristics of the assets. In this study, we investigate whether manufacturing firms in Indonesia that have high productivity have a high level of liquidity. This study uses data from manufacturing firms listed on the Indonesia Stock Exchange in the period of 2008 to 2017. We estimate the productivity level of the firm using the Generalized Method of Moments (GMM) and effects of productivity on the liquidity of the firm using the linear panel model. Results show that manufacturing firms in Indonesia with high productivity levels tend to have a higher level of liquidity than firms with lower levels of productivity. Even if Indonesia already adopt a market-based financial system, other types of financial frictions cause that firms allocate more of their resource to liquid assets than to fixed assets. Even though the effects of misallocation became weaker, misallocations of resources in manufacturing firms Indonesia are still found from a robustness test.JEL Classifications: G15, G31, G32DOI: https://doi.org/10.26905/jkdp.v23i2.3191